Endogenous thrombopoietin promotes non‐small‐cell lung carcinoma cell proliferation and migration by regulating EGFR signalling. Issue 12 (26th April 2020) - Zou, Zifang; Fan, Xiaoxi; Liu, Yang; Sun, Yanbin; Zhang, Xin; Sun, Guanghao; Li, Xuehao; Xu, Shun
Abstract: Thrombopoietin (TPO) is a haematopoietic cytokine mainly produced by the liver and kidneys, which stimulates the production and maturation of megakaryocytes. In the past decade, numerous studies have investigated the effects of TPO outside the haematopoietic system; however, the role of TPO in the progression of solid cancer, particularly lung cancer, has not been well studied. Exogenous TPO does not affect non‐small‐cell lung cancer (NSCLC) cells as these cells show no or extremely low TPO receptor expression; therefore, in this study, we focused on endogenous TPO produced by NSCLC cells. Immunohistochemical analysis of 150 paired NSCLC and adjacent normal tissues indicated that TPO was highly expressed in NSCLC tissues and correlated with clinicopathological parameters including differentiation, P‐TNM stage, lymph node metastasis and tumour size. Suppressing endogenous TPO by small interfering RNA inhibited the proliferation and migration of NSCLC cells. Moreover, TPO interacted with the EGFR protein and delayed ligand‐induced EGFR degradation, thus enhancing EGFR signalling. Notably, overexpressing TPO in EGF‐stimulated NSCLC cells facilitated cell proliferation and migration, whereas no obvious changes were observed without EGF stimulation. Our results suggest that endogenous TPO promotes tumorigenicity of NSCLC via regulating EGFR signalling and thus could be a therapeutic target for treating NSCLC.